2017
DOI: 10.1038/nature23881
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb-like proteins link the PRC2 complex to CpG islands

Abstract: The Polycomb repressive complex 2 (PRC2) mainly mediates transcriptional repression1,2 and plays essential roles in various biological processes including the maintenance of cell identity and proper differentiation. Polycomb-like proteins (PCLs), including PHF1, MTF2 and PHF19, are PRC2 associated factors that form sub-complexes with PRC2 core components3, and have been proposed to modulate PRC2’s enzymatic activity or its recruitment to specific genomic loci4–13. Mammalian PRC2 binding sites are enriched in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
336
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(362 citation statements)
references
References 41 publications
20
336
5
1
Order By: Relevance
“…One possibility is that H2AK119ub1 could directly disrupt RNA Polymerase II activity (Stock et al, 2007;Zhou et al, 2008), as recently suggested by in vitro transcription assays, in which incorporation of H2AK119ub1 into recombinant chromatin templates blocked transcription (Aihara et al, 2016;Nakagawa et al, 2008). Alternatively, PRC1 catalytic activity and H2AK119ub1 could have an indirect effect on transcription, for example by creating a binding site for reader proteins which would then elicit repression (Ali et al, 2018;Cooper et al, 2016;Qin et al, 2015;Richly et al, 2010;Zhang et al, 2017). In addition, incorporation of a bulky ubiquitin moiety may interfere with deposition of other histone modifications that facilitate gene expression (Nakagawa et al, 2008;Yuan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility is that H2AK119ub1 could directly disrupt RNA Polymerase II activity (Stock et al, 2007;Zhou et al, 2008), as recently suggested by in vitro transcription assays, in which incorporation of H2AK119ub1 into recombinant chromatin templates blocked transcription (Aihara et al, 2016;Nakagawa et al, 2008). Alternatively, PRC1 catalytic activity and H2AK119ub1 could have an indirect effect on transcription, for example by creating a binding site for reader proteins which would then elicit repression (Ali et al, 2018;Cooper et al, 2016;Qin et al, 2015;Richly et al, 2010;Zhang et al, 2017). In addition, incorporation of a bulky ubiquitin moiety may interfere with deposition of other histone modifications that facilitate gene expression (Nakagawa et al, 2008;Yuan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies have identified two subtypes of PRC2 complexes with distinct targeting modules (reviewed in Laugesen et al, 2019;Yu et al, 2019). The PRC2.1 complex contains PCL proteins, which have been shown to bind to non-methylated CpG-rich DNA and methylated histone tails (Ballare et al, 2012;Brien et al, 2012;Cai et al, 2013;Li et al, 2017;Musselman et al, 2012a;Perino et al, 2018), while the PRC2.2 complex contains the JARID2 subunit, which has been recently implicated in direct recognition of H2AK119ub1 (Cooper et al, 2016;Kalb et al, 2014). Based on the major reductions in SUZ12 binding and H3K27me3 levels in the tamoxifen-treated PRC1 CPM cells, we wanted to test whether occupancy of PRC2.1 and PRC2.2 was differentially affected by loss of PRC1 catalytic activity.…”
Section: Prc2 Binding and Deposition Of H3k27me3 At Polycomb Target Smentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that DNA methylation plays an important role in restricting H3K27me3 to unmethylated CpG islands. This is evident from preferential localization of H3K27me3 to endogenous The EMBO Journal Isoform-specific DNMT3A function Massimiliano Manzo et al and ectopic unmethylated CpG-rich regions (Tanay et al, 2007;Mikkelsen et al, 2007;Mohn et al, 2008;Mendenhall et al, 2010;Jermann et al, 2014;Wachter et al, 2014), the identification of PRC complex members that preferentially bind unmethylated CpGs and GC-rich sequences (Farcas et al, 2012;Wu et al, 2013;Li et al, 2017), and numerous studies that reported spreading of H3K27me3 in the absence of DNA methylation (Lynch et al, 2011;Brinkman et al, 2012;Marks et al, 2012;Reddington et al, 2013;Jermann et al, 2014;King et al, 2016). We suggest that the balance between DNMT3A1 and TET activity is required to fine-tune the distribution of methylated and unmethylated CpGs and for restricting Polycomb domain boundaries to the promoters of developmentally regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the genome-wide binding sites of PRCs in mESCs have been well documented, the molecular mechanisms for recruiting PRCs to specific genomic loci in mammalian cells have not been fully elucidated (Laugesen, Hojfeldt, and Helin 2019). A variety of factors, such as JARID2 and MTF2, have been reported to mediate the PRC2 recruitment (Landeira et al 2010;Pasini et al 2010;Shen et al 2009;Casanova et al 2011;Li et al 2017;Oksuz et al 2018). On the other hand, histone lysine demethylase 2b (KDM2B) recruits a non-canonical PRC1.1 variant to the unmethylated CpG islands (CGIs) in mammalian cells through its CxxC-zinc finger (CxxC-ZF) domain (Wu, Johansen, and Helin 2013;He et al 2013;Farcas et al 2012).…”
Section: Introductionmentioning
confidence: 99%